Counterblast - McLuhan, Marshall 1911-1980. (London : Rapp + whiting, 1969)
"In the same year that Wyndham Lewis published 'Self Condemned', Marshall McLuhan took inspiration from Lewis's journal BLAST and produced COUNTERBLAST, intended, like 'Self Condemned', to shake the city of Toronto out of its smugness, complacency, and spiritual torpor."--Publisher's website (viewed Aug. 4, 2011).
Keywords: Mass media; Technology and civilization; Mass media; Technology and civilization; Massenmedien